1312 The relationship between the post-traumatic stress syndrome and the occupational stress among the firefighters in korea. (24th April 2018) - Ram Kim, A; Sung, Joo Hyun; Cho, Seong Woo; Jeong, Kyoung Sook; Ahn, Yeon-Soon; Sim, Chang Sun
Abstract : Introduction: Traumatic stress like experience in witnessing a suicide or accidents can cause post-traumatic stress disorder (PTSD). Firefighters are exposed to traumatic stresses due to their professional nature. It is known that dealing with extra stress after the event can be a risk factor in development of the disease. Thus, we aim to study to see whether occupational stress can act as a risk factor in development of PTSD. Methods: 310 among total 315 professional firefighters were given written informed consents and answered self -reported questionnaires. Impact of Event Scale-Revision (IES-R), Life Event Checklist (LEC) and Korean Occupational Stress Scale (KOSS) questionnaires were used to assess the PTSD and determine the level of occupational stress. SPSS 21.0 was used for all statistical analysis. Results: According to the IES-R questionnaire, 75 out of 310 subjects (24.2%) were in risk of developing PTSD. The LEC score which is designed to screen one's experience of potentially traumatic events was significantly high in the PTSD risk group compared to no risk group (p=0.008). Total KOSS score of PTSD risk group (49.21±10.90) was also significantly higher than that of no risk group (45.17±10.86) (p=0.005). Conclusion: The prevalence of PTSD was significantly higher in firefighters than general population in several studies, and result of our study also corresponds well. Furthermore we could confirm that the more impact traumatic stress one has experienced in life, the more likely it is to develop PTSD and occupational stress is playing as a risk factor in the development of the disease. By identifying the level of occupational stress and the impact of traumatic event using simple self-reported questionnaires, it would be easier to detect the people who are in risk of developing PTSD and take early medical intervention to prevent the progression of PTSD.